REFORMING OF THE SYSTEM OF LEGAL PROTECTION IN THE SPHERE OF INTELLECTUAL PROPERTY IN UKRAINE - Volodymyr Yu. Poplavskyi; Tetiana А. Todoroshko; Vera V. Нerasіuta (Alfred Nobel University Journal of Law)
The article is devoted to the reform of the system of legal protection in the field of intellectual property and the improvement of legislation in Ukraine, its compliance with international standards. The authors note that it is necessary to improve the system of intellectual property legal protection, with using world experience. Also, they pay attention that in Ukraine there is an insufficient level of protection of intellectual property rights. The authors note that education and formation of public consciousness are quite important. It is proposed to conduct a large-scale educational campaign, which will be aimed at creating a legal culture among the population of Ukraine, and providing basic knowledge about the rights of intellectual property owners and mechanisms for its protection, in particular on the Internet. Some pirate sites offering counterfeit and pirated products openly operate in Ukraine, the number of such sites is even increasing, which is explained by the imperfection of the current legislation. It is expedient to resolve such issues by improving the legislative framework, including strengthening legal liability for violations in the field of intellectual property, in particular, the distribution of pirated products. And it is also necessary to expand the rights of law enforcement agencies in the direction of providing additional organizational and legal mechanisms for identifying and countering violations of intellectual property rights. It also draws attention to the fact that the problem is relevant and needs to be addressed now. An example is that in our country a judicial institution has been created. It is the Supreme Court for Intellectual Property, which is still not functioning. This indicates that Ukraine is characterized by the practice of delaying court cases. Therefore, the question of the functioning of the High Court of Intellectual Property is important and urgent. It is necessary to improve the mechanism of judicial protection and the system of bodies for the protection of intellectual property. For further economic development and improvement of the international image of our state, as well as for faster accession to the EU, we must not postpone this issue, but continue to improve our legislation.